New Trends in Swedish Educational Research - Englund, Thomas (Scandinavian Journal or Educational Research, 2006)
What new tendencies can be made out in Swedish educational research in the last three decades? Briefly, the following developments are described: In the 1970s, a long-prevailing emphasis on quantitative research was challenged by a number of different qualitative methods. Traditional sociology of education, meanwhile, was challenged by the new sociology of education. During the 1980s, the dominant trend was a “didacticisation‷0i0k0i0n0d0x of educational research, and here two main strands can be discerned, based in phenomenography and curriculum theory. Didactics very soon made its presence felt in educational policy, and in a major evaluation of Swedish educational research the two largely didactics-based traditions of “teaching and learning‷0i0k0i0n0d0x and “curriculum theory‷0i0k0i0n0d0x were identified as internationally the most significant. In the 1990s, educational research took a “linguistic turn‷0i0k0i0n0d0x—involving a wide-ranging shift in emphasis towards language and communication—with the result that new perspectives emerged. In addition, the philosophy of education experienced a powerful renaissance, partly as a reflection of the new focus on language and communication, but also in other respects, leading to a reawakening of interest in both classical and modern philosophy (of education).
Keywords: Suède; utilisation des recherches